2014
DOI: 10.1093/europace/euu165
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation in patients with ischaemic stroke in the Swedish national patient registers: how much do we miss?

Abstract: Despite the high specificity, AF diagnosis in the Swedish Patient Register assessed in the population of ischaemic stroke patients and age- and gender-matched control subjects has modest sensitivity, which may result in underestimating prevalent and incident AF cases if only register data are used for identification of subjects with AF in epidemiology studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
4
14
0
Order By: Relevance
“…In total, 2588 ECG’s were reviewed with a median number of ECG recordings per person of four (IQR 1–9) [8]. New onset atrial fibrillation was found in 39 (17%) of the stroke patients (Hazard ratio 1.49, 95% confidence interval 0.09–2.35, p  = 0.121) as previously reported [2, 8]. The median time to AF onset was 3.2 (IQR 1.3 to 5.9) years.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…In total, 2588 ECG’s were reviewed with a median number of ECG recordings per person of four (IQR 1–9) [8]. New onset atrial fibrillation was found in 39 (17%) of the stroke patients (Hazard ratio 1.49, 95% confidence interval 0.09–2.35, p  = 0.121) as previously reported [2, 8]. The median time to AF onset was 3.2 (IQR 1.3 to 5.9) years.…”
Section: Resultssupporting
confidence: 55%
“…The Cause of Death Register is also provided by the Swedish National Board of Health and Welfare and contains information (since 1961) from death records, including underlying causes of death and up to 20 contributory causes of death coded to the current edition (ICD-10). The presence of the ICD-10 code I48 in the Swedish national registers identified AF diagnosis with high specificity and modest sensitivity as we showed recently in a validation study on patients with ischemic stroke enrolled in the LSR [2]. …”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…The presence of ICD-10 I48 code in the Swedish national registers identified AF diagnosis with high specificity and modest sensitivity as we showed recently in a validation study on patients with ischemic stroke enrolled in the LSR [19].…”
Section: New Onset Afsupporting
confidence: 59%
“…It is a further strength that the validity of the Patient register has been shown to be good with increasing positive predictive values through the last decades [30]. For atrial fibrillation, the positive predictive value is estimated at 93-97% [30,31].…”
Section: Discussionmentioning
confidence: 98%